Digital discourse in the pro-Israel products boycott campaign on Instagram - Sila Sitti Romlah; Yopi Kusmiati; Riaz Ahmad Saeed (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
This study examines the form of digital discourse in the campaign to boycott pro-Israel products on Instagram, focusing on how influencers construct and disseminate messages as a means of public education and information. Grounded in a constructivist paradigm, this qualitative research employs a digital discourse analysis approach. Data were collected through digital observation, digital documentation, in-depth interviews, and literature review. The research subjects consist of BuyCut movement influencers, namely Habib Ares, Ustadh Amar, Teh Rika, Bang Amal, and Kak Shahaja, while the object of analysis is their digital discourse on Instagram. The study applies digital discourse analysis theory proposed by Patricia Bou-Franch and Pilar Garcés-Conejos Blitvich, particularly the concepts of multimodality, face and identity, and language and media ideology. The findings reveal that influencers strategically integrate text, images, videos, audio, posters, and hashtags to construct persuasive boycott narratives. They position their identities according to their backgrounds and values, framing the campaign through religious, nationalistic, and social awareness perspectives. The study concludes that digital discourse on Instagram functions as a collaborative, multimodal space for ideological expression and mobilization in boycott campaigns. ***** Studi ini meneliti bentuk wacana digital dalam kampanye boikot produk pro-Israel di Instagram, dengan fokus pada bagaimana para influencer membangun dan menyebarkan pesan sebagai sarana pendidikan dan informasi publik. Berlandaskan paradigma konstruktivis, penelitian kualitatif ini menggunakan pendekatan analisis wacana digital. Data dikumpulkan melalui observasi digital, dokumentasi digital, wawancara mendalam, dan tinjauan pustaka. Subjek penelitian terdiri dari para influencer gerakan BuyCut yaitu Habib Ares, Ustaz Amar, Teh Rika, Bang Amal, dan Kak Shahaja, sementara objek analisisnya adalah wacana digital mereka di Instagram. Studi ini menerapkan teori Analisis Wacana Digital yang dikemukakan oleh Patricia Bou-Franch dan Pilar Garcés-Conejos Blitvich, khususnya konsep multimodalitas, wajah dan identitas, serta bahasa dan ideologi media. Temuan menunjukkan bahwa para influencer secara strategis mengintegrasikan teks, gambar, video, audio, poster, dan tagar untuk membangun narasi boikot yang persuasif. Mereka memposisikan identitas mereka sesuai dengan latar belakang dan nilai-nilai mereka, membingkai kampanye melalui perspektif keagamaan, nasionalistik, dan kesadaran sosial. Studi ini menyimpulkan bahwa wacana digital di Instagram berfungsi sebagai ruang kolaboratif dan multimodal untuk ekspresi ideologis dan mobilisasi dalam kampanye boikot.